Pengenalan Jenis Bunga Anggrek Menggunakan Metode Color Local Binary Pattern dan Support Vector Machine - Debby Meliani Prayogo; Kartika Gunadi; Endang Setyati (Jurnal Infra, 2020)
Orchid flowers are the flowering plants with the most types or species. One of them is the moon orchid flower which is one of the three national flowers in Indonesia. Orchid flowers can be found in city parks and many tourist attractions because of its beauty. However, people will certainly have difficulty in recognizing the type of orchid. Therefore, a program is made to help people in identifying the types of orchids that are around. Orchid flower recognition has already been researched to recognize the texture of its flower. However, this study uses 25 species of orchids that is from Indonesia to be recognized.You Only Look Once (YOLO) method is used for detecting flower objects in the image. Before classifying the orchid species, the background image need to be removed using Image Segmentation. The Color Local Binary Pattern descriptor is used to get the texture of the image through several colorspaces, namely grayscale, RGB, HSI, YIQ, and oRGB. Support Vector Machine is then used to recognize the type of orchid.The result of this program can recognize the species of orchids in the picture. From the test results using the researcher’s dataset show an accuracy of 30.7% using color space grayscale, 37% using color space RGB, 34.6% using color space HSI, 41% using color space YIQ, and 40.2% using color space oRGB in recognizing the species of orchid.